Developmental or adult-onset deletion of neurotensin receptor-1 from dopamine neurons differentially reduces body weight - Perez-Bonilla, Patricia; Ramirez-Virella, Jariel; Menon, Pooja; Troyano-Rodriguez, Eva; Arriaga, Sydney K.; Makela, Anna; Bugescu, Raluca; Beckstead, Michael J.; Leinninger, Gina M. (Frontiers in Neuroscience, 2022)
Central neurotensin signaling via neurotensin receptor-1 (NtsR1) modulates various aspects of physiology, including suppressing feeding and promoting locomotor activity that can support weight loss. However, it remains unclear when and where NtsR1 expression contributes to control of body weight vs. other effects. We previously showed that activating ventral tegmental area (VTA) dopamine (DA) neurons that express NtsR1 promotes weight loss. We therefore hypothesized that deleting NtsR1 from DA neurons would promote weight gain by increasing food intake and decreasing physical activity. In contrast, developmental deletion of NtsR1 from DA neurons (by crossing DATCre mice with NtsR1flox/flox mice) had no impact on the feeding or body weight of mice fed a chow diet, though it augmented locomotor activity. Developmental deletion of NtsR1 from DA neurons protected mice from diet-induced obesity, but not via altering feeding or physical activity. Given that NtsR1 may exert distinct roles within development vs. adulthood, we then examined the impact of adult-onset deletion of NtsR1 from VTA DA neurons. We injected adult NtsR1flox/flox mice in the VTA with adeno associated virus to Cre-dependently delete NtsR1 in the VTA (VTAR1Null mice) and compared them to mice with intact NtsR1 (Controls). Again, in contrast to our hypothesis, VTAR1Null mice gained less weight than Controls while on normal chow or high fat diets. Moreover, VTAR1Null mice exhibited blunted feeding after fasting, suggesting a role for NtsR1 in adult VTA DA neurons in coordinating energy need and intake. Altogether, these data suggest that intact expression of NtsR1 in DA neurons is necessary for appropriate regulation of body weight, but a lack of NtsR1 in the developing vs. adult DA system protects from weight gain via different mechanisms. These findings emphasize the need for temporal and site-specific resolution to fully understand the role of NtsR1 within the brain.